ORGANIZATION OF WINTER ROAD MAINTENANCE (Perner's Contacts, 2015)
The paper presents on the winter maintenance of roads. Introduces basic laws of the Czech Republic for winter maintenance. Acquaints with owners and managers of roads and rank the importance of winter maintenance. Also presents the various technologies of winter maintenance. Phase states winter maintenance - the measures before the start of winter maintenance, proper winter maintenance winter maintenance and evaluation. Within its own winter maintenance are possibilities of its optimization.
Keywords: roads, winter maintenance technology, graph theory, vehicle routes, winter maintenance